A Study on Working from Home During the Covid-19 Pandemic; Satisfaction, Challenges, And Productivity of Employees - Shirtode, Madhuri Bhagwat; Madam, Manisha Jagtap (ASEAN Journal of Educational Research and Technology, 2022)
This study investigated how professionals are collaborating online in various countries. Various aspects of this shift in working culture have been examined like employee satisfaction levels, challenges related to telecommunicating, and perceived productivity of working remotely during the COVID-19 outbreak situation. This study has employed an exploratory research design. This study has obtained secondary data from various articles published in journals and conference proceedings, books, news media, and websites. And, primary data via an online survey using a set of a semi-structured questionnaire. The convenience sampling technique has been used to choose a sample of professionals working from home during the COVID-19 pandemic. All in all, the results have shown that most of the participants are fairly satisfied with working from home during the COVID-19 pandemic. work flexibility is the main factor contributing to this satisfaction. Moreover, the majority of the respondents have cited internet connectivity and maintaining a regular schedule as the biggest challenges of telecommuting. This is one of the few studies to focus on working grim homes during the COVID-19 pandemic. The findings have vital implications for working professionals, organizations, and HR policymakers.